A Mixed Method Approach to Assessing the Feasibility of Implementing the Ottawa Paramedic Physical Abilities Test (TM) in the Australian Context. - Sheridan, Samantha; Pope, Rodney; MacPhee, Renee S.; MacQuarrie, Alexander; Fischer, Steven; Buzza, Gavin; Stack, Hannah; Bolton, Lyndal; Grevell, Jacob; Sheridan, Christopher Tony; Buckman, Jacinta; Rayner, Russell (Internet Journal of Allied Health Sciences & Practice, 2026)
Introduction: There is a need for evidence-based pre-employment physical fitness test standards in paramedic organisations. This study aimed to assess the feasibility of implementing an existing, international, standardised pre-employment paramedic physical capacity test, the Ottawa Paramedic Physical Abilities Test (OPPATTM), in the Australian context. Methods: In this mixed-method feasibility study, 12 undergraduate paramedicine students completed two generic predictive tests - a three-minute step test (3MST20) and a grip strength test - and two physical employment tests: the Ottawa Paramedic Physical Abilities Test (OPPATTM) and the New South Wales Ambulance Test (NSWAT) -- and a brief perception questionnaire after each test. Physiological data were collected during testing using Hexoskin® devices and analysed descriptively. Qualitative data relating to participant and investigator perceptions of the feasibility of the tests for use in the Australian paramedicine context were analysed through content analysis. Results: Of the 12 participants, six met the criteria to begin all physical tests. Two successfully completed all physical tests, measured by current pre-employment requirements. Participants reported feeling underprepared for the current physical employment standards and were uncertain about the physical capacity demands of the paramedic role. All the physical tests were considered, in part, feasible based on participant performance, cost, time requirements for test setup, and perceived job relatedness criteria; however, the OPPATTM was considered most relevant to the paramedic role. Conclusion: The OPPATTM is adaptable and likely feasible for application in Australian ambulance services as a physical pre-employment test that could be implemented by universities within curricula for student physical preparation. Current student paramedics, however, may not be sufficiently physically prepared for the test. Further work is needed to ensure standardised and appropriate student paramedic preparation, and preemployment testing specific to the paramedic role, supporting both staff and patient safety.